2007
DOI: 10.1074/jbc.m611770200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Induces Glucose Uptake in 3T3-L1 Adipocytes through A Gab1/Phosphatidylinositol 3-Kinase/Glut4 Pathway

Abstract: Adipose tissue is a source of hepatocyte growth factor (HGF), and circulating HGF levels have been associated with elevated body mass index in human. However, the effects of HGF on adipocyte functions have not yet been investigated. We show here that in 3T3-L1 adipocytes HGF stimulates the phosphatidylinositol (PI) 3-kinase-dependent protein kinase B (PKB) activity, AS160 phosphorylation, Glut4 translocation, and consequently, glucose uptake. The initial steps involved in HGF-and insulininduced glucose uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 39 publications
2
30
0
1
Order By: Relevance
“…It has recently been reported that HGF enhances glucose transport in pancreatic beta cells and adipocytes (3,6). The current studies demonstrate for the first time that HGF also acutely increases glucose uptake in mouse soleus muscle ex vivo and rat L6 myotubes in vitro and that this effect is translated into an augmentation of glucose utilization, but not storage, in L6 myotubes.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…It has recently been reported that HGF enhances glucose transport in pancreatic beta cells and adipocytes (3,6). The current studies demonstrate for the first time that HGF also acutely increases glucose uptake in mouse soleus muscle ex vivo and rat L6 myotubes in vitro and that this effect is translated into an augmentation of glucose utilization, but not storage, in L6 myotubes.…”
Section: Discussionsupporting
confidence: 48%
“…HGF has also been shown to up-regulate the Na ϩ /glucose co-transporter SGLT1 and the facilitative glucose transporter Glut-5 in rat intestine epithelial cells (5). Furthermore, HGF promotes Glut-4 translocation to the cellular membrane and enhances glucose uptake through phosphatidylinositol 3-kinase (PI3K) activation in 3T3-L1 adipocytes (6). Taken together, these studies demonstrate HGFmediated regulatory effects on glucose transport in three different cells types: beta cells, intestinal epithelial cells, and adipocytes.…”
mentioning
confidence: 99%
“…Growth factors, including HGF, EGF and TNF-, have been shown to increase glucose utilization in a variety of cells (Bertola et al, 2007;Boussouar and Benahmed, 1999;Hsu and Sabatini, 2008;Perdomo et al, 2008;Véga et al, 2002). Furthermore, Kaplan and colleagues (Kaplan et al, 2000) have shown that HGF also enhances glycolysis and oxidative phosphorylation in murine mammary cells.…”
Section: Hgf Increases Proton Production Inducing Acidification Of Tmentioning
confidence: 99%
“…Proteins (50 g) were separated by SDS-PAGE using a 10% resolving gel. The Western blotting was performed as previously described (27). The proteins were probed with anti-OPN (AKm2A1) or anti-GAPDH (FL-335) antibodies (Santa Cruz Biotechnology, Santa Cruz, CA) at 1 g/ml.…”
Section: Methodsmentioning
confidence: 99%